2017
DOI: 10.1016/j.jcm.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Unresolved Congenital Torticollis and Its Consequences: A Report of 2 Cases

Abstract: Objective: The purpose of this report was to describe the clinical presentation and case management of 2 children with congenital torticollis. Clinical Features: Two male children (ages 6 and 10 years) presented to a chiropractic clinic with a history of congenital torticollis. They showed signs and symptoms of postural deficiency and developmental delay: posterior plagiocephaly, facial scoliosis, head tilt, compensatory thoracic scoliosis, decreased range of motion in the cervical spine, palpable decreased se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…CMT is relatively often observed not only when the foetus is in the breech position, but also in children of primiparas [ 46 ]. The data obtained in this study confirmed the latter and revealed that the incidence of congenital muscular torticollis was higher in first-born children.…”
Section: Discussionmentioning
confidence: 99%
“…CMT is relatively often observed not only when the foetus is in the breech position, but also in children of primiparas [ 46 ]. The data obtained in this study confirmed the latter and revealed that the incidence of congenital muscular torticollis was higher in first-born children.…”
Section: Discussionmentioning
confidence: 99%